Learning from Stock Prices and Economic Growth - Peress, Joel (Review of Financial Studies, 2014)
A competitive stock market is embedded into a neoclassical growth economy to analyze the interplay between the acquisition of information about firms, its partial revelation through stock prices, capital allocation, and income. The stock market allows investors to share their costly private signals in a cost-effective incentive-compatible way. It contributes to economic growth by raising total factor productivity (TFP). A calibration indicates the effect on TFP to be large but that on income to be modest. Several predictions on the evolution of real and financial variables are derived. Finally, the growth impact of two common forms of investor irrationality, overconfidence and inattention, are analyzed.